Analysis of Informatics Engineering Students’ Learning Interest in a Linear Algebra Course - Ayu Ismi Hanifah; Masruroh Masruroh (Universitas Islam Lamongan, 2022)
Learning is an interactive process between educators and students in a certain lesson. One of the affective aspects that has a role in the learning process is learning interest. This learning interest has an extremely important role and has a great impact on students in a lesson. This research intended to comprehend Informatics Engineering students’ learning interest in a Linear Algebra course. The subjects of this research were Informatics Engineering Students of Universitas Islam Lamongan, with a total of 53 students. This research method was a qualitative descriptive method. The data source in this research came from the questionnaire of students’ learning interests in a Linear Algebra course. The data analysis in this research used four learning interest criteria including feelings of pleasure, attention, interest, and involvement. The results of the analysis that was obtained from this research got an average of: 71.89% for the criteria of pleasure feeling; 72.36% for the attention criteria; 71.79% for the interest criteria; and 71.79% for the involvement criteria with a total average of 71.96%. It can be concluded that students' learning interest in the Linear Algebra course was in the high category.